Efforts to Improve Product Competitiveness of Baso Aci Tata Snack in Kediri, East Java through Re-Packaging - Indrasari, Lolyka Dewi; Komari, Ana; Tripariyanto, Afif Yudha; Rahayuningsih, Sri; Santosa, Heribertus Budi (Universitas Muhammadiyah Magelang, 2021)
Packaging is the process of packaging a product so that it has appeal. This attractiveness is an effort to increase product competitiveness, so that potential buyers are interested in consuming, using and recommending it to the public. The Baso Aci production house Tata Snack has the main product in the form of aci meatball with a plain vacuum sealer packaging model. The problem raised was designing the baso aci packaging based on the voting results of the participants. Participants in this activity were 16 employees and owners of the Tata Snack meatball business. The activity was carried out on December 16, 2020, starting with the preparation of activities and implementation of activities. The methods used were lecturing, giving question and answer, discussing and voting. This community service produced packaging designs with standing pouch printing items and screen prints containing information about Baso aci.